Characterization of gas turbine ingested sand particles based on electrostatic signal. (May 2022) - Sun, Jianzhong; Jiang, Heng; Yang, Caiqiong; Liu, Ruochen
Particle ingestion into a gas turbine can have serious effects on both performance and engine in-service reliability. Thus there exists a need for in situ monitoring and characterizing particulate matter entering an aircraft engine inlet for the purposes of engine damages estimation and prognosis. This paper presents the initial development of Ingested Debris Monitoring System (IDMS) signal processing method of characterizing the ingested particles. A theoretical analysis and simulation study were carried out to study the relationships between the characteristics of the ingested sand particles and the features of the IDMS signal both in frequency- and time-domain. A Finite-Element Modeling (FEM) for the IDMS Sensor was developed, then the validated FEM modeling was used for simulation experiments of particles ingestion under various conditions of different particle moving speeds, concentrations and charge-to-mass ratios. Results of the theoretical analysis and simulation study demonstrates the feasibility and effectiveness of the proposed method to provide real time information characterizing the size and concentration of ingested sand particles, and will serve as an impetus to carry out further research.